An electrolyte-gated transistor for the monitoring of a CRISPR/Cas activity - Pierre Guermonprez; Le Tu Anh; Louis Renaud; Pierre Nioche; Eric Krejci; Aurélie Alleaume-Butaux; Nicolas Battaglini; Vu Thi Thu; Sébastien Sanaur; Benoît Piro (Biosensors and Bioelectronics: X)
Detection of Ribonucleic acids (RNA) is a critical step in the identification of viral or bacterial infections in humans and animals. Reverse transcriptase-polymerase chain reaction (RT-PCR) remains the gold standard, but clustered regularly interspaced short palindromic repeats linked to a Cas endoribonuclease particle (CRISPR/Cas) have recently revolutionized the recognition step of two RNAs, i.e. the CRISPR-RNA (crRNA) and the target, providing a much better selectivity compared to the naked hybridization on which RT-PCR is based. Here, we combine the high efficiency of the CRISPR/Cas13a system with the transduction and amplification capabilities of an electrolyte-gated graphene field-effect transistor (EGGFET) for the detection of specific RNA sequences. In these devices, fabricated on flexible plastic substrates, the active material (reduced graphene oxide, rGO) is deposited by printing and then functionalized with Au nanoparticles decorated with polyU RNA reporter strands. In this system, the CRISPR/Cas13a complex acts as a catalyst: in the presence of a specific RNA target sequence, the enzymatic function is activated and the polyU RNA reporter strands are cleaved from the Au nanoparticles, inducing a loss of negative charges on the rGO layer. This phenomenon leads to measurable changes in the transfer curve of the transistors. These sensors were tested for the detection of a SARS-CoV-2 RNA sequence and showed a linear response in the range of 10−7 - 102 ng μL−1 with an estimated limit of detection of 10 fM. This work is an important milestone in the development of the next generation of point-of-care RNA sensors.